Integrating Heavy Metal Adsorption on Organic Waste Materials into Defense and Security Studies: A Sustainable Approach - Sekarini, Artanti; Ariyanti, Dita (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2023)
This study aims to examine the plausible fusion of heavy metal adsorption through lignin derived from organic waste materials into the realm of defense and safety studies. This study underscores the imperative nature of addressing heavy metal pollution within defense operations and environmental conservation. It proposes utilizing lignin, derived from organic waste materials, as a pivotal solution to combat heavy metal contamination. By synthesizing insights from existing literature, this research delves into lignin's potential as a highly effective adsorbent tailored for the defense sector. The study illuminates lignin's versatility in interacting with heavy metals through multifaceted adsorption mechanisms, offering a sustainable strategy to mitigate environmental harm while fortifying national resilience. Derived from diverse biomass sources, including peanut shells, cocoa pod shells, coconut shells, rice husks, and empty oil palm fruit bunches, lignin exhibits promising adsorption capacities attributed to its ample surface area and diverse functional groups. Emphasizing a holistic perspective, this research advocates for an integrated approach that harnesses lignin's robust adsorption capabilities to meet the specific demands of defense and security, envisioning a future that is both secure and sustainable. This is attributed to the inherent properties of lignin, such as its abundant surface area and diverse functional groups. The lignin derived from these biomasses offers a versatile and effective solution, showcasing high adsorption potential due to its ability to accommodate various heavy metal ions and contribute to sustainable environmental remediation practices. By synergizing lignin's robust adsorption attributes with the requisites of defense and security, this research advocates for a comprehensive approach, fostering a vision of a secure and sustainable future.